2020
DOI: 10.1101/2020.05.22.20109231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of country-wide coronavirus mortality with demographics, testing, lockdowns, and public wearing of masks (Update August 4, 2020)

Abstract: Background. There is wide variation between countries in per-capita mortality from COVID-19 (caused by the SARS-CoV-2 virus). Determinants of this variation are not fully understood. Methods. Potential predictors of per-capita coronavirus-related mortality in 198 countries were examined, including age, sex ratio, obesity prevalence, temperature, urbanization, smoking, duration of infection, lockdowns, viral testing, contact tracing policies, and public mask-wearing norms and policies. Multivariable… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 73 publications
(59 reference statements)
0
25
0
1
Order By: Relevance
“…4 and 5). Leffler et al (2020) reported in a global study that internal lockdown requirements were not associated with mortality, but that in countries that recommended use of face masks early on at the national level, the COVID-19 death rate was lower than expected.…”
Section: Discussionmentioning
confidence: 91%
“…4 and 5). Leffler et al (2020) reported in a global study that internal lockdown requirements were not associated with mortality, but that in countries that recommended use of face masks early on at the national level, the COVID-19 death rate was lower than expected.…”
Section: Discussionmentioning
confidence: 91%
“…More quality studies from scientists will help support public health officials when they are encouraging or mandating mask wearing. More data continues to emerge supporting the use of masks; for example, one recent study examined the different sources of variation among over 200 countries in per-capita mortality due to COVID-19, and reported that duration of mask wearing by the public was negatively associated with mortality [ 64 ]. Thus, masks may be here to stay for the foreseeable future and may not just have application for COVID-19, but for severe flu seasons and for potential future respiratory epidemics/pandemics.…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the need for public health measures that can be applied very widely to prevent widespread community transmission. Research is increasingly suggesting that masks, including non-medical masks, may be able to significantly reduce COVID-19 transmission (Eikenberry, et al, 2020;Stutt, et al, 2020;Leung, et al, 2020;Leffler, et al, 2020) and led the World Health Organization (WHO) and Center for Disease Control (CDC) to recommend universal facial covering and mask use for the general public. At the same time, the global reach of the pandemic saw a shortage of personal protective equipment for healthcare providers, requiring conservation of the supply of N95 respirators and surgical masks for the healthcare providers.…”
Section: Introductionmentioning
confidence: 99%